Altruistic self-removal of health-compromised honey bee workers from their hive - RUEPPELL, O; HAYWORTH, M.K; ROSS, N.P (Journal of evolutionary biology, 2010)
Social insect colonies represent distinct units of selection. Most individuals evolve by kin selection and forgo individual reproduction. Instead, they display altruistic food sharing, nest maintenance and self-sacrificial colony defence. Recently, altruistic self-removal of diseased worker ants from their colony was described as another important kin-selected behaviour. Here, we report corroborating experimental evidence from honey bee foragers and theoretical analyses. We challenged honey bee foragers with prolonged CO₂ narcosis or by feeding with the cytostatic drug hydroxyurea. Both treatments resulted in increased mortality but also caused the surviving foragers to abandon their social function and remove themselves from their colony, resulting in altruistic suicide. A simple model suggests that altruistic self-removal by sick social insect workers to prevent disease transmission is expected under most biologically plausible conditions. The combined theoretical and empirical support for altruistic self-removal suggests that it may be another important kin-selected behaviour and a potentially widespread mechanism of social immunity.